Yellow phosphorus slag-phosphogypsum-yellow phosphorus tailing mortar-based filling material as well as preparation method and application thereof

Through specific formula design and the use of composite activators, the problems of insufficient fluidity and strength of solid wastes such as phosphate tailings, phosphogypsum and yellow phosphorus slag in filling materials were solved, and high-fluidity, low-bleeding rate and high-strength filling materials suitable for mine filling were prepared, achieving efficient resource utilization of solid waste and environmental benefits.

CN120774685APending Publication Date: 2025-10-14贵州绿色产业技术研究院
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202511196609.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-26
Publication Date
2025-10-14

AI Technical Summary

Technical Problem

In the existing technology, solid wastes such as phosphate tailings, phosphogypsum and yellow phosphorus slag have low fluidity, high water seepage rate and insufficient strength in the prepared filling materials, and cannot be effectively used in mine filling, which limits their scope of use.

Method used

Through specific formula design, cementitious materials are prepared from solid wastes such as yellow phosphorus slag, phosphogypsum and yellow phosphorus tailings. Combined with composite activators and water-retaining agents, the fluidity, water bleeding rate and setting time are adjusted to form CSH gel and calcium aluminate, thereby improving the strength and density of the material and achieving efficient resource utilization.

Benefits of technology

The prepared filling material has high fluidity, low water seepage rate and high strength, is suitable for mine filling, realizes the resource utilization of solid waste, reduces the risk of environmental pollution, and has a simple process flow and low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005565242870000061
    Figure BDA0005565242870000061
  • Figure BDA0005565242870000071
    Figure BDA0005565242870000071
  • Figure BDA0005565242870000072
    Figure BDA0005565242870000072
Patent Text Reader

Abstract

The invention discloses a yellow phosphorus slag-ardealite-yellow phosphorus tailing slurry-based filling material and a preparation method and application thereof.The yellow phosphorus slag-ardealite-yellow phosphorus tailing slurry-based filling material is prepared from, by weight, 80-91 parts of aggregate and 9-20 parts of cementing material, and the cementing material is prepared from, by weight, 45-60 parts of yellow phosphorus slag, 5-10 parts of phosphogypsum, 5-10 parts of yellow phosphorus tailing slurry and 5-10 parts of a binder. The aggregate comprises the following components in parts by weight: 15-25 parts of slag, 15-20 parts of modified phosphogypsum, 3-5 parts of bentonite, 3-5 parts of talcum powder, 5-10 parts of a composite exciting agent, 0.1-0.5 part of a water-retaining agent and 0.1-0.5 part of a flocculating agent, the composite exciting agent comprises the following components in parts by weight: 30-40 parts of carbide slag, 10-20 parts of calcium formate, 10-20 parts of sulfate and 5-10 parts of silica fume, and the aggregate is yellow phosphorus tailing mortar with the slurry concentration of 66-68%. According to the filling material, solid waste resource utilization is achieved, and meanwhile the high bleeding rate, the high fluidity and the high strength can be achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of mine filling, in particular to a yellow phosphorus slag-phosphogypsum-yellow phosphorus tailings mortar-based filling material and a preparation method and application thereof. Background Art

[0002] Phosphate tailings are solid waste generated during phosphate ore beneficiation. The production of 1 ton of phosphate concentrate produces approximately 0.44 tons of phosphate tailings. The production of 1 ton of phosphoric acid generates approximately 4-5 tons of phosphogypsum, and the production of 1 ton of yellow phosphorus produces 8-10 tons of yellow phosphorus slag. These solid wastes, including phosphate tailings, phosphogypsum, and yellow phosphorus slag, contain elements such as fluorine and phosphorus. Their accumulation not only wastes land resources but also pollutes soil and water resources, harming the ecological environment. Therefore, effective utilization of these solid wastes is necessary to maximize resource utilization and minimize environmental pollution. Currently, the main uses of phosphate tailings, phosphogypsum, and yellow phosphorus slag are in the production of building materials, fertilizers, and fillers. GB 175-2023, "General Portland Cement," stipulates that yellow phosphorus slag can no longer be added as an admixture to cement clinker, further reducing its utilization rate. To improve the utilization of these wastes, efforts are underway to address the challenges of increasing the utilization of yellow phosphorus slag, phosphogypsum, and yellow phosphorus tailings. Existing technologies include using solid waste as raw material for filling materials. This not only consumes large amounts of phosphate rock solid waste, improves its comprehensive utilization rate, and avoids occupying land resources, but also reduces environmental pollution and lowers the cost of solid waste management for enterprises. However, currently prepared filling materials are not suitable for mine filling due to their low fluidity, high water bleeding rate, and need for improvement in strength. Therefore, the application scope of filling materials obtained through resource recovery is greatly limited, which also restricts the sustainable development of solid waste.

[0003] Therefore, there is an urgent need to provide a method for resource processing of yellow phosphorus slag, phosphogypsum, and yellow phosphorus tailings while making the resulting filling material have high fluidity, low water seepage rate, and high strength so that it can be used as a mine filling material and its application range is improved. Summary of the Invention

[0004] To address the shortcomings of existing technologies, the present invention proposes a yellow phosphorus slag-phosphogypsum-yellow phosphorus tailings mortar-based filling material, its preparation method, and its application. Through a unique formulation, the present invention utilizes solid wastes such as yellow phosphorus slag, yellow phosphorus tailings, and phosphogypsum generated by phosphorus chemical plants to produce the filling material, achieving efficient disposal of solid waste. The resulting filling material exhibits high fluidity, low water bleeding, and high strength, making it suitable for use as a mine filling material.

[0005] The present invention provides a yellow phosphorus slag-phosphogypsum-yellow phosphorus tailings mortar-based filling material, which comprises 80-91 parts of aggregate and 9-20 parts of cementitious material in parts by weight;

[0006] The cementing material comprises the following components by weight parts: yellow phosphorus slag 45-60 parts, such as 45, 48, 50, 52, 55, 60 parts; slag 15-25 parts, such as 15, 18, 20, 22, 25 parts; modified phosphogypsum 15-20 parts, such as 15, 16, 17, 18, 20 parts; bentonite 3-5 parts, such as 3, 4, 5 parts; talcum powder 3-5 parts, such as 3, 4, 5 parts; composite activator 5-10 parts, such as 5, 6, 7, 8, 9, 10 parts; water retaining agent 0.1-0.5 parts, such as 0.1, 0.2, 0.3, 0.4, 0.5 parts; flocculating agent 0.1-0.5 parts, such as 0.1, 0.2, 0.3, 0.4, 0.5 parts;

[0007] The composite activator comprises the following components by weight parts: calcium carbide slag 30-40 parts, such as 30, 32, 34, 36, 38, 40 parts; calcium formate 10-20 parts, such as 10, 12, 14, 16, 18, 20 parts; sulfate 10-20 parts, 10, 12, 14, 16, 18, 20 parts; such as silica ash 5-10 parts, such as 5, 6, 7, 8, 9, 10 parts;

[0008] The aggregate is yellow phosphorus tailings slurry with a slurry concentration of 66-68%, and the slurry concentration is the percentage of the mass of solid substances in the slurry to the total mass of the slurry.

[0009] Due to the filling pipe transportation length problem during filling, the filling material is required to have good fluidity and retarding property, so it is necessary to adjust the fluidity and setting time of the filling body. The present application obtains a cementing material containing C-S-H gel (calcium silicate hydrate gel) and Aft (ettringite) through raw material compounding and specific composite activation of alkali-sulfate by depolymerization-polymerization reaction, and adjusts the fluidity, bleeding rate and setting time of the cementing material according to different filling requirements by adjusting the specific formula ratio of solid waste and composite activator and adding water retaining agent and flocculating agent, while ensuring good compatibility of the cementing material with the aggregate, so that the formation of C-S-H gel and ettringite further improves the overall density and strength of the filling material when the cementing material fills the gap of the aggregate, and finally a mine filling material with fluidity, bleeding rate and later strength meeting the requirements is obtained.

[0010] Yellow phosphorus slag contains a large amount of silicon and calcium elements, but at the same time, the soluble phosphorus and fluorine in the yellow phosphorus slag will cause it to have a certain slow setting property, and it cannot be added in large quantities to cement as an admixture, which hinders the large-scale utilization of yellow phosphorus slag. The present invention uses yellow phosphorus slag as the main component to prepare a cementitious material, and at the same time carries out a specific formula design, which can achieve efficient utilization of yellow phosphorus slag, wherein the main components of the slag are active ingredients such as calcium, silicon, and aluminum, which can form calcium aluminate with sulfate in the modified phosphogypsum during the hydration process, and also generate CSH gel, thereby improving the strength of the filling material. The main function of talcum powder is to provide lubricity for the filling slurry, which is more convenient for long-distance transportation of the material in the pipeline, and the particle size of talcum powder is small, which can also increase the density of the filling slurry; on the other hand, the present invention also carries out a special design for the composite activator, wherein the calcium carbide slag can provide an alkali for the components. The calcium ions in the calcium formate react with silica fume and sulfate to accelerate the hydration reaction of phosphate slag and slag, forming more CSH gel and ettringite. The formate in calcium formate interferes with the formation of Ca(OH)2, promoting the formation of uniform CSH gel and optimizing the formation rate of ettringite. It also lowers the freezing point of water, promoting the hydration reaction in the low-temperature environment underground and further improving the strength of the filling material after solidification. At the same time, free calcium ions can combine with phosphorus and fluoride ions to form insoluble products such as calcium fluoride and calcium phosphate. The free phosphorus, fluoride, and heavy metal ions are solidified through chemical chelation and adsorption and encapsulation between bentonite and flocculants. The water retention agent can further reduce the water bleeding rate and maintain the pumping stability of the slurry.

[0011] Furthermore, the sulfate includes one or more of aluminum sulfate, sodium sulfate, and anhydrous calcium sulfate.

[0012] Furthermore, the water-retaining agent includes one or more of xanthan gum, guar gum, and hydroxypropyl methylcellulose ether. The carboxyl or hydroxyl groups in the water-retaining agent can combine with water molecules through hydrogen bonds to form a stable hydration layer, increase the viscosity of the system, and reduce water loss and migration.

[0013] Furthermore, the flocculant is cationic polyacrylamide. Since cationic polyacrylamide carries a positive charge, it can partially adsorb free phosphate and fluoride ions. Its long-chain structure can also form a bridging structure. The resulting three-dimensional structure can increase the flocculation volume and accelerate sedimentation and separation. When used in conjunction with a water-retaining agent, it can not only lock in moisture but also strengthen the particle network of the filling material slurry, ensuring both fluidity and stability.

[0014] Furthermore, the mass ratio of the aggregate to the cementitious material is (4-10):1. The ratio of aggregate to cementitious material is inversely proportional to the compressive strength of the filling material and can be selected according to the strength required for filling.

[0015] Furthermore, the particle size of the modified phosphogypsum, yellow phosphorus slag, and slag is 45≤D90≤70μm, and the particle size is tested using GB / T19077-2016 "Particle Size Analysis Laser Diffraction Method"; among them, the activity of slag is ≥95%, and the activity of yellow phosphorus slag is ≥80%. As active ingredients, the smaller the particle size of slag and yellow phosphorus slag, the larger the specific surface area, and the more complete the hydration reaction, which is conducive to the improvement of mechanical properties. The larger the particle size of modified phosphogypsum will affect the activity and is not conducive to the improvement of mechanical properties.

[0016] Furthermore, the particle size of the talc powder is 5≤D90≤15 μm, and the particle size of the bentonite is 45≤D90≤70 μm.

[0017] Furthermore, the silica fume in the composite activator has a particle size of 1≤D90≤2μm, wherein the SiO2 content is ≥94%, and the SiO2 content is measured using X-ray fluorescence spectrometry (XRF); the carbide slag has a particle size of 45≤D90≤70μm, wherein the Ca(OH)2 content is ≥80%, and the Ca(OH)2 content is measured using X-ray fluorescence spectrometry (XRF); the calcium formate purity is ≥98%, and the aluminum sulfate purity is ≥90%. The larger particle size of carbide slag affects the activity and is not conducive to improving the mechanical properties. The silica fume has finer particles and higher activity, which can improve the interface bonding between the filler and the matrix.

[0018] Furthermore, the preparation method of the modified phosphogypsum comprises the following steps:

[0019] Add 1-3% of lime milk by weight to phosphogypsum, stir evenly and adjust the pH to between 7 and 9. After aging for 24-48 hours, calcine at 150-180°C for 160-200 minutes. After the low-temperature calcination, place it in a dry place for 24-26 hours, and then ball mill and sieve it.

[0020] By chemically neutralizing and low-temperature calcining the phosphogypsum, the dihydrate gypsum is converted into hemihydrate gypsum, further improving the strength of the filling material.

[0021] The present invention also provides a method for preparing the filling material, comprising the following steps:

[0022] Drying: Dry yellow phosphorus slag, slag, fly ash and carbide slag in an oven at 110-120℃ to ensure that the moisture content of each raw material is ≤1%;

[0023] Ball milling: ball mill the raw materials of the gelling material and the composite activator separately and sieve them;

[0024] Stirring: Stir the yellow phosphorus tailings slurry evenly to ensure that no particles settle to the bottom and affect the slurry concentration;

[0025] Mixing: The raw material components of the cementitious material, the composite activator, the aggregate and the admixture are weighed respectively in parts by weight, and the powder obtained by uniformly mixing them is the mine filling material.

[0026] The present invention also provides an application of the filling material as a mine filling material, comprising: adding water to the mine filling material to mix the mixture to form a slurry, and then transporting the slurry to a mine for solidification and filling.

[0027] In summary, compared with the prior art, the present invention achieves the following technical effects:

[0028] (1) The yellow phosphorus slag-phosphogypsum-yellow phosphorus tailings mortar-based filling material provided by the present invention has high strength.

[0029] (2) The yellow phosphorus slag-phosphogypsum-yellow phosphorus tailings mortar-based filling material provided by the present invention has a low water seepage rate.

[0030] (3) The yellow phosphorus slag-phosphogypsum-yellow phosphorus tailings mortar-based filling material provided by the present invention has high fluidity and transportation stability.

[0031] (4) The yellow phosphorus slag-phosphogypsum-yellow phosphorus tailings mortar-based filling material provided by the present invention can fix phosphorus and fluoride ions in solid wastes such as yellow phosphorus slag, phosphogypsum, and yellow phosphorus tailings, thereby avoiding pollution to the environment and having environmental benefits.

[0032] (5) The raw materials used in the yellow phosphorus slag-phosphogypsum-yellow phosphorus tailings mortar-based filling material provided by the present invention are all solid waste materials, thus realizing the resource utilization of solid waste.

[0033] (6) The method for preparing the yellow phosphorus slag-phosphogypsum-yellow phosphorus tailings mortar-based filling material provided by the present invention has a simple process flow and low production cost. DETAILED DESCRIPTION

[0034] In order to help those skilled in the art better understand the solutions of the present invention, the technical solutions in the embodiments of the present invention are clearly and completely described below. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without making any creative efforts should fall within the scope of protection of the present invention.

[0035] Example

[0036] The present invention is further described below with reference to specific examples and comparative examples. The following specific examples are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the following examples, and are particularly not limited to the types of the various component raw materials used in the following specific examples.

[0037] 1. Sources of Raw Materials in Examples and Comparative Examples

[0038] Unless otherwise specified, the solid waste raw materials used in the examples and comparative examples of the present application are all commercially available. The different particle sizes of each solid waste raw material are obtained by ball milling and sieving. The remaining components are all commercially available unless otherwise specified.

[0039] Table 1 Raw materials used in Examples and Comparative Examples

[0040]

[0041]

[0042] Table 2 Composite exciter formula (unit is weight parts)

[0043] Composite Activator #1 Composite Activator #2 Composite Activator #3 Carbide slag #1 30 Carbide slag #2 40 Calcium carbide slag #3 30 sulfate 10 20 10 silica fume 5 10 5 calcium formate 10 20 10

[0044] Table 3 Cementitious material formula (unit is weight part)

[0045]

[0046]

[0047] The preparation method of the modified phosphogypsum in the embodiment of the present invention comprises the following steps:

[0048] Add 1-3% of lime milk by weight to phosphogypsum, stir evenly and adjust the pH to 8. After aging for 24 hours, calcine at 160°C for 180 minutes. After the low-temperature calcination, place it in a dry place for 24 hours, and then ball mill and sieve according to the required particle size.

[0049] The preparation method of the yellow phosphorus slag-phosphogypsum-yellow phosphorus tailings mortar-based filling material in the embodiments of the present invention and the comparative examples comprises the following steps:

[0050] Drying: Dry yellow phosphorus slag, slag, fly ash and carbide slag in an oven at 110-120℃ to ensure that the moisture content of each raw material is ≤1%;

[0051] Ball milling: ball mill the raw materials of the gelling material and the composite activator separately and sieve them;

[0052] Stirring: Stir the yellow phosphorus tailings slurry evenly to ensure that no particles settle to the bottom and affect the slurry concentration;

[0053] Mixing: The raw material components of the cementitious material, the composite activator, the aggregate and the admixture are weighed respectively in parts by weight, and the powder obtained by uniformly mixing them is the mine filling material.

[0054] 2. Various performance tests

[0055] (1) Determination of setting time: Test according to GB / T1346-2011 “Test method for standard consistency, setting time and stability of cement”.

[0056] (2) Uniaxial compressive strength test: The test was carried out in accordance with the Standard for Test Methods for Basic Properties of Building Mortar JGJ / T 70-2009.

[0057] (3) Determination of total phosphorus concentration: Tested according to the "Ammonium molybdate spectrophotometry method" GB / T11893-1989 and the "Ion chromatography method" GB / T5085.3-2007.

[0058] (4) Determination of fluoride ion concentration: Test according to the “Determination of fluoride in water - Ion-selective electrode method” GB / T 7484-1987.

[0059] (5) Fluidity and water seepage rate test: Test in accordance with the Standard for Performance Test Methods of Ordinary Concrete Mixtures GB / T50080-2016.

[0060] Table 4 Examples and Comparative Examples Technical Scheme (units are parts by weight)

[0061]

[0062] Table 5 Technical effects of embodiments and comparative examples

[0063]

[0064] In Examples 1-6, filling materials were prepared using both a specifically formulated cementitious material and aggregate. The cementitious material comprised solid waste raw materials, modified phosphogypsum, a specific composite activator, and a flocculant. All of the filling materials produced in Examples 1-6 exhibited high fluidity, low water bleeding, and high strength, achieving resource utilization of solid waste while also achieving environmental benefits. Comparative Example 1, unlike Example 3, used unmodified phosphogypsum. Consequently, the resulting filling materials failed to simultaneously achieve low water bleeding, high fluidity, and high strength.

[0065] Based on the test data of compressive strength, setting time, total phosphorus, fluoride ion concentration, water bleeding rate and fluidity of the filling material in Table 5, the yellow phosphorus slag-phosphogypsum-yellow phosphorus tailings mortar-based filling material prepared by Examples 1-6 has obvious advantages over the comparative example and can effectively meet the high standards of customers and the market.

[0066] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A yellow phosphorus slag-phosphogypsum-yellow phosphorus tailings mortar-based filling material, characterized in that: By weight, it includes 80-91 parts of aggregate and 9-20 parts of cementitious material; The gelling material comprises the following components by weight: 45-60 parts of yellow phosphorus slag, 15-25 parts of slag, 15-20 parts of modified phosphogypsum, 3-5 parts of bentonite, 3-5 parts of talc, 5-10 parts of composite activator, 0.1-0.5 parts of water retaining agent, and 0.1-0.5 parts of flocculant; The composite activator comprises the following components by weight: 30-40 parts of carbide slag, 10-20 parts of calcium formate, 10-20 parts of sulfate, and 5-10 parts of silica fume; The aggregate is yellow phosphorus tailings mortar with a slurry concentration of 66-68%.

2. The filling material according to claim 1, characterized in that The water-retaining agent includes one or more of xanthan gum, guar gum, and hydroxypropyl methylcellulose ether.

3. The filling material according to claim 1, characterized in that The flocculant is cationic polyacrylamide.

4. The filling material according to claim 1, characterized in that The mass ratio of the aggregate to the cementitious material is (4-10):

1.

5. The filling material according to claim 1, characterized in that The particle size of the modified phosphogypsum, yellow phosphorus slag and slag is 45≤D90≤70μm.

6. The filling material according to claim 1, characterized in that The particle size of the talc powder is 5≤D90≤15 μm, and the particle size of the bentonite is 45≤D90≤70 μm.

7. The filling material according to claim 1, characterized in that The particle size of the silica fume in the composite activator is 1≤D90≤2μm, wherein the SiO2 content is ≥94%, and the particle size of the carbide slag is 45≤D90≤70μm, wherein the Ca(OH)2 content is ≥80%.

8. The filling material according to claim 1, characterized in that The preparation method of the modified phosphogypsum comprises the following steps: Add 1-3% of lime milk by weight to phosphogypsum, stir evenly and adjust the pH to between 7 and 9. After aging for 24-48 hours, calcine at 150-180°C for 160-200 minutes. After the low-temperature calcination, place it in a dry place for 24-26 hours, and then ball mill and sieve it.

9. The method for preparing the filling material according to any one of claims 1 to 8, characterized in that: The steps include: Drying: Dry yellow phosphorus slag, slag and carbide slag in an oven at 110-120℃ to ensure that the moisture content of each raw material is ≤1%; Ball milling: ball mill the raw materials of the gelling material and the composite activator separately and sieve them; Stirring: Stir the yellow phosphorus tailings slurry evenly to ensure that no particles settle to the bottom and affect the slurry concentration; Mixing: The raw material components of the cementitious material, the composite activator, the aggregate and the admixture are weighed respectively in parts by weight, and the powder obtained by uniformly mixing them is the mine filling material.

10. Use of the filling material according to any one of claims 1 to 8 as a mine filling material, characterized in that: The method comprises adding water to the mine filling material to form a slurry, and then transporting the slurry to the mine for solidification and filling.

Citation Information

Patent Citations

  • Lithium slag-based geopolymer filling material as well as preparation method and application thereof

    CN118754530A

  • Yellow phosphorus tailing-based mine filling material and application thereof

    CN119490313A

  • Mine filling cement material capable of cementing high-content phosphate tailings as well as preparation method and use method of mine filling cement material

    CN119528536A